Religious Moderation Education in the Relationship between Islamic Boarding Schools and the Chinese Ethnicity in the Chinatown of Rembang City - Husna Nashihin; Edi Purnama; Triana Hermawati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
In a socio-cultural context, 94% of the population in Lasem is of Chinese ethnic descent, and 4% are of native descent, which is why Lasem is better known as